DNA Damage Response Differentially Affects BoHV-1 Gene Transcription in Cell Type-Dependent Manners - Linke Tang; Weifeng Yuan; Shitao Li; Xiuyan Ding; Liqian Zhu (Biomedicines, 2022)
Bovine herpesvirus 1 (BoHV-1), an important pathogen of cattle, is also a promising oncolytic virus. Recent studies have demonstrated that the virus infection induces DNA damage and DNA damage response (DDR), potentially accounting for virus infection-induced cell death and oncolytic effects. However, whether the global DDR network affects BoHV-1 productive infection remains to be elucidated. In this study, we show that global DDR induced by ultraviolet (UV) irradiation prior to BoHV-1 infection differentially affected transcription of immediate early (IE) genes, such as infected cell protein 0 (bICP0) and bICP22, in a cell-type-dependent manner. In addition, UV-induced DDR may affect the stabilization of viral protein levels, such as glycoprotein C (gC) and gD, because the variation in mRNA levels of gC and gD as a consequence of UV treatment were not in line with the variation in individual protein levels. The virus productive infection also affects UV-primed DDR signaling, as demonstrated by the alteration of phosphorylated histone H2AX (γH2AX) protein levels and γH2AX formation following virus infection. Taken together, for the first time, we evidenced the interplay between UV-primed global DDR and BoHV-1 productive infection. UV-primed global DDR differentially modulates the transcription of virus genes and stabilization of virus protein. Vice versa, the virus infection may affect UV-primed DDR signaling.